2014
DOI: 10.1111/ppl.12182
|View full text |Cite
|
Sign up to set email alerts
|

Measure for measure: determining, inferring and guessing auxin gradients at the root tip

Abstract: The plant hormone auxin is transported from sites of synthesis to sites of action. Auxin responses are mediated by fast (non-transcriptional) and slow (transcriptional; ubiquitinylation) responses, which affect physiological changes at cellular and organismal scales. As such, auxin transport vectors regulate programmed and plastic growth responses to optimize growth and development. Here we address some common problems in extrapolating 'universal' understanding of auxin transport streams from analyses of loss-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 99 publications
(161 reference statements)
0
8
0
Order By: Relevance
“…Auxin originating from or redirected at the root cap controls transcriptional oscillations that initiate lateral root primordia (Van Norman, 2015; Xuan et al, 2015) within the xylem pole pericycle which surrounds the central vascular cylinder (Dolan et al, 1993; Dubrovsky et al, 2000; Casimiro et al, 2001; Van Norman et al, 2013; Kircher and Schopfer, 2016). Excision and labeling experiments in Arabidopsis demonstrate that auxin involved in both lateral root initiation and emergence is initially shoot derived and transported in a rootward stream between 5 and 7 d after germination (Busse and Evert, 1999; Bhalerao et al, 2002; Lewis et al, 2007; Swarup et al, 2008; Peer et al, 2014). The requirement for auxin synthesis at the root apex as seedlings mature was more definitively demonstrated when root growth of quadruple yucca auxin biosynthesis mutants was rescued by exogenous auxin in the media, but not by auxin overproduction in the shoot (Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Auxin originating from or redirected at the root cap controls transcriptional oscillations that initiate lateral root primordia (Van Norman, 2015; Xuan et al, 2015) within the xylem pole pericycle which surrounds the central vascular cylinder (Dolan et al, 1993; Dubrovsky et al, 2000; Casimiro et al, 2001; Van Norman et al, 2013; Kircher and Schopfer, 2016). Excision and labeling experiments in Arabidopsis demonstrate that auxin involved in both lateral root initiation and emergence is initially shoot derived and transported in a rootward stream between 5 and 7 d after germination (Busse and Evert, 1999; Bhalerao et al, 2002; Lewis et al, 2007; Swarup et al, 2008; Peer et al, 2014). The requirement for auxin synthesis at the root apex as seedlings mature was more definitively demonstrated when root growth of quadruple yucca auxin biosynthesis mutants was rescued by exogenous auxin in the media, but not by auxin overproduction in the shoot (Chen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…toward the roots) and is then redirected upward (i.e. toward the shoots) at the root cap ( Ohwaki and Tsurumi, 1976 ; Tsurumi and Ohwaki, 1978 ; Hasenstein and Evans, 1988 ; Petrášek and Friml, 2009 ; Peer et al , 2014 ). However, IAA biosynthesis was also observed to occur in maize and Arabidopsis root tips ( Feldman, 1980 ; Ljung et al , 2005 ; Chen et al , 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the mechanism controlling IAA levels in maize roots. Some studies have indicated that at least some of the IAA in the root apex is derived from the upper region of roots ( Berleth and Sachs, 2001 ; Peer et al , 2014 ). However, recent studies on Arabidopsis have indicated that IAA is also synthesized in root apices ( Ljung et al , 2005 ; Stepanova et al , 2008 ; Chen et al , 2014 ; Yang et al , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Visualization of cellular auxin gradients using auxin-responsive reporter lines has been widely utilized to dissect the role of auxin gradient formation in physiological response of plant. 911 As an alternative approach, using an artificial auxin gradient system would benefit studies of the positional impact of auxin levels on diverse type of cells and tissue in plants.…”
mentioning
confidence: 99%